TANGGUNG JAWAB BADAN ARBITRASE SYARIAH NASIONAL (BASYARNAS) DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Sakti, Muthia; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2017)
National Sharia Arbitration Board established by the Majelis Ulama Indonesia. The reason the founding of the National Sharia Arbitration Board with their idea of Islamic Economics is characterized by the development of Islamic banking, such as the birth of the Islamic Bank, which certainly has a dispute must be resolved sharia and sharia, so the need to involve other parties to mediate in resolving the dispute sharia. In this thesis will be discussed on the responsibility of the National Sharia Arbitration Board (BASYARNAS) in resolving disputes regarding the authority of Islamic Banking and Religious Court against the execution and cancellation of the decision of the Arbitration Sharia in Indonesia.